Analisis Ekonomi Politik dan Gender: Studi Kasus Peran Perempuan dalam Pembangunan Ekonomi di Indonesia - Wardana, Rian Ismi; Magriasti, Lince (Multiverse: Open Multidisciplinary Journal, 2024)
This study explores the intersection of political economy and gender through an in-depth case study of women's roles in economic development in Indonesia. The research addresses the critical question of how women's participation in economic activities influences and is influenced by broader economic policies and political structures. Employing a mixed-methods approach, the study combines quantitative data analysis with qualitative interviews to provide a comprehensive view of the subject. The findings reveal that while there have been significant strides in women's economic participation, substantial barriers remain due to entrenched patriarchal norms and inadequate policy support. The study concludes that for Indonesia to achieve sustainable economic growth and gender equality, a more inclusive approach to economic policymaking is essential. This involves not only addressing structural barriers but also fostering an environment where women's contributions are recognized and valued. The research underscores the importance of integrating gender perspectives into economic policies to enhance both economic and social outcomes.